The backsliding of democracy in the EU: an analysis on the perception of corruption in the Member States pre- and post-pandemic - Marta Pérez-Gabaldón; Nuria Hernández-García; Carlos González-Tormo (Political Research Exchange)
One of the main obstacles the Rule of Law and democracy are currently facing – for which the Rule of Law is a necessary precondition – is corruption. However, this is a multicausal and complex phenomenon very difficult to measure and often substituted with perceptions-based indexes. This research will dive into what affects the perception of corruption (CPI index) in the European Union pre (2019) and post (2021) pandemic. Literature willl be analised in order to establish the main economic and political factors that might be related to the perception of corruption and, following previous studies, will examine if there is anything that can be used as a predictor of higher levels of perception of corruption and what role the pandemic has had on them. The quantitative analysis made through model regressions and cluster analysis will construct relevant conclusions. In general and economical terms, it will show how relevant shadow economy is regarding the perception of corruption before and after COVID-19’s impact. In political terms, the variables influencing to the perception of corruption the most – ideology of the government and its party composition – will be replaced, following the impact of the pandemic, by the gender of the cabinet leadership.